Designing a Conceptual Model for the Development of Health Tourism in the Country: A Grounded Theory Approach. - Estarki, Samira Loghman (International Journal of Travel Medicine & Global Health, 2025)
Introduction: The health tourism industry is regarded as one of the most lucrative and competitive sectors in the world. In recent years, this industry has experienced significant growth, particularly in developing countries. Research indicates that, despite various studies in the field of health tourism, there is no comprehensive model that accurately delineates all dimensions and components of this domain. Therefore, it is essential to design a comprehensive model of health tourism and the influencing factors on it, as well as to develop strategies derived from these factors. This research was conducted with the aim of designing a model for the development of health tourism using a qualitative approach based on grounded theory. A model that examines this industry from various dimensions and provides strategies for its development. Methods: In terms of purpose, this research is fundamental, and in terms of nature, it falls under the category of qualitative research (Grounded Theory). Regarding the results, it is part of exploratory studies. The statistical population under study consists of eleven experts, including senior managers and specialists from health tourism centers in Tehran. The tool for collecting research data is interviews, and the selection of research participants was conducted using the purposeful sampling method. For data analysis, the method of content analysis was employed, based on open coding, axial coding, and selective coding. Results: Based on the results obtained, the development of health tourism in the country is influenced by causal conditions (quality of healthcare services, cost, credibility of medical services, health accommodation services, tourism services, and transportation), contextual reasons (natural, social, legal, and political factors), intervening factors (organizational, insurance affairs, banking affairs, and informal and underground activities), a central category (health tourism development), strategies (advertising, government support for the private sector, health tourism training, HIS development, consultation and relationship development, infrastructure development, and creating tourist loyalty and trust), and consequences (improving the quality of life, economic development, promotion of community culture, and environmental development). The results indicate that the research model is at an acceptable level. Conclusion: It is expected that the conceptual model presented in this research will serve as a suitable roadmap for the development of the country's health tourism industry.